Efficacy and tolerability of 16% subcutaneous immunoglobulin compared with 20% subcutaneous immunoglobulin in primary antibody deficiency. (7th July 2015) - Niebur, H B; Duff, C M; Shear, G F; Nguyen, D; Alberdi, T K; Dorsey, M J; Sleasman, J W
Summary: Multiple subcutaneous immunoglobulin (SCIG) products are available to treat primary antibody deficiency (PAD). The efficacy and tolerability of 16% SCIG (Vivaglobin ® ) was compared with 20% SCIG (Hizentra ® ) in PAD subjects. The study was a prospective, single-centre, open-label study of PAD subjects transitioning Vivaglobin to equivalent Hizentra doses, rounded to the nearest vial size. Comparisons included immunoglobulin (Ig)G levels; tetanus, varicella and Streptococcus pneumoniae titres; adverse events (AEs), annual infection rate and quality of life during 8 weeks of Vivaglobin and 24 weeks of Hizentra. Thirty-two subjects (aged 2–75 years) participated. Rounding to the nearest Hizentra vial size resulted in a 12·8% (± 2·9%) increase in SCIG dose. Median immunoglobulin (Ig)G level following 8 weeks of Vivaglobin was similar to 24 weeks of Hizentra (1050 versus 1035 mg/dl, respectively; P =  0·77). Both products had similar protective titres to tetanus, varicella and serotypes of S. pneumoniae, which were variable but well above protective levels. After 12 weeks of Hizentra, subjects reported fewer local site reactions compared with Vivaglobin. Switching products resulted in increased systemic AEs in some subjects but, overall, not significantly higher than during Vivaglobin treatment. Average infusion time decreased from 104·7 min (3·3 sites) with Vivaglobin to 70·7 min (2·2 sites) with Hizentra ( P =  0·0005). Acute serious bacterial infections were similar. Treatment satisfaction was superior with Hizentra. Hizentra and Vivaglobin have similar pharmacokinetics and efficacy. Although transition to a different SCIG product initially increased AEs, Hizentra is well tolerated and can be infused more rapidly and with fewer sites compared to Vivaglobin.